Modelling of the Water Absorption Kinetics and Determination of the Water Diffusion Coefficient in the Pith of Raffia vinifera of Bandjoun, Cameroon - E. Tiaya Mbou; E. Njeugna; A. Kemajou; N. R. Tagne Sikame; D. Ndapeu (Advances in Materials Science and Engineering)
The present work focuses on the study of the water absorption phenomenon through the pith of Raffia vinifera along the stem. The water absorption kinetics was studied experimentally by the gravimetric method with the discontinuous control of the sampling mass at temperature of 30°C. The samples of 70 mm × 8 mm × 4 mm were taken from twelve sampling zones of the stem of Raffia vinifera. The result shows that the percentage of water absorption of the pith of Raffia vinifera increases from the periphery to the center in the radial position and from the base to the leaves in the longitudinal position. Fick’s second law was adopted for the study of the water diffusion. Eleven models were tested for the modelling of the water absorption kinetics and the model of Sikame Tagne (2014) is the optimal model. The diffusion coefficients of two stages were determined by the solution of the Fick equation in the twelve sampling zones described by Sikame Tagne et al. (2014). The diffusion coefficients decreased from the center to the periphery in the radial position and from the base to the leaves in the longitudinal position.